2017
DOI: 10.1002/chem.201700617
|View full text |Cite
|
Sign up to set email alerts
|

An Optically Active Polymer for Broad‐Spectrum Enantiomeric Recognition of Chiral Acids

Abstract: Recognition of enantiomers of chiral acids by anion-π or lone pair-π interactions has not yet been investigated but is a significant and attractive challenge. This study reports an optically active polymer-based supramolecular system with capabilities of discriminating enantiomers of various chiral acids. The polymer featuring alternate π-acidic naphthalenediimides (NDIs) and methyl l-phenylalaninates in the backbone exhibits an unprecedented slow self-assembly process that is susceptible to perturbation by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…The time‐dependent CD spectra showed that AcO − had a significant influence on the self‐assembly and the chiral supramolecular architectures of PNDI (Figure b). The negative CD signal at 382 nm becomes significantly weaker with time, which is contrary to the behavior in the absence of anions (Scheme a). The positive CD signal for PNDI at 334 nm disappears in the presence of AcO − .…”
Section: Methodscontrasting
confidence: 57%
See 3 more Smart Citations
“…The time‐dependent CD spectra showed that AcO − had a significant influence on the self‐assembly and the chiral supramolecular architectures of PNDI (Figure b). The negative CD signal at 382 nm becomes significantly weaker with time, which is contrary to the behavior in the absence of anions (Scheme a). The positive CD signal for PNDI at 334 nm disappears in the presence of AcO − .…”
Section: Methodscontrasting
confidence: 57%
“…Polymer anion receptors, which usually supply multivalent and cooperative supramolecular interactions with anions, have attracted considerable attention owing to their unique features of signal amplification and enhanced sensitivity versus non‐polymeric systems . Recently, we found a supramolecular system based on the chiral polymer PNDI whose feature of slow self‐assembly was prone to disturbance by external chiral acids (Scheme ) . The disturbance of self‐assembly gives the polymer the capacity for enantiomeric recognition of chiral acids and salts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lone pair-π [1][2][3][4][5][6][7] and anion-π [1,[8][9][10][11][12][13][14][15][16][17][18][19] interactions are emergent noncovalent forces whose occurrence has recently been recognized in both synthetic architectures [8,20,21] and biomolecular structures [4,[22][23][24][25][26] and are now taken into account for the construction of new functional materials [27][28][29][30][31][32][33][34], receptors [35][36][37][38][39][40][41][42][43] carriers [44][45][46]…”
Section: Introductionmentioning
confidence: 99%